PENAMPILAN DIAGNOSTIK SOLUBLE TRASFERRIN RECEPTOR (sTfR) UNTUK SKRINING DEFISIENSI BESI PADA ANAK USIA 6 BULAN - 5 TAHUN - , M. Nur; , dr. Tri Ratnaningsih, M.Kes, SpPK-K. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Iron deficiency is a major cause of anemia in children. Iron deficiency affect child growth and decrease immune response. Gold standard for examination of iron deficiency is invasive and not suitable for screening iron deficiency. Biochemical and hematological parameters have several limitations. Biochemical and hematological parameters have limitations. Soluble transferrin receptor (sTfR) is a clinical marker of erythropoietic activity and sensitive to changes in serum iron status. It is not influenced by inflammation and infection. STfR levels start to increase in the second stage of iron deficiency. This study aims to determine the use of sTfR for screening iron deficiency in children aged 6 months - 5 years in Yogyakarta. This was a diagnostic study for screening with a cross-sectional design using ferritin as a gold standard. Subjects were healthy children aged 6 months-5 years of Posyandu toddler in Yogyakarta and obtaining consent from the parents. sTfR was examined with imunoturbidimetri method using cobas C 311. Ferritin was checked using the Elecsys 1010 instrument with electrochemiluminescens method. ROC curve analysis was performed using SPSS version 17. Sensitivity, specificity, positive predictive value (NRP), negative predictive value (NRN), accuracy, and positive likelihood ratio (LR +) and negative likelihood ratio (LR-) were calculated with a 2x2 table. There were 86 subjects who meet the inclusion and exclusion criteria. Levels of sTfR the cut-off 4.44 mg / L had a sensitivity of 75%, specificity 71.8%, 21.4% NRP